Semiconductor Radiation Detectors Device Physics - Lutz, Gerhard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
Starting from basic principles, the autor, whose own contributions to these developments have been significant, describes the rapidly growing field of modern semiconductor detectors used for energy and position measurement radiation. This development was stimulated by requirements in elementary particle physics where it has led to important scientific discoveries. It has now spread to many other fields of science and technology. The book is written in a didactic way and includes an introduction to semiconductor physics. The working principles of semiconductor radiation detectors are explained in an intuitive way, followed by formal quantitative analysis. Broad coverage is also given to electronic signal readout and to the subject of radiation damage. The book is the first to comprehensively cover the semiconductor radiation detectors currently in use. It is useful as a teaching guide and as a reference work for research and applications.
Semiconductor Physics -- Semiconductors -- Basic Semiconductor Structures -- Semiconductor Detectors -- Semiconductors as Detectors -- Detectors for Energy and Radiation-Level Measurement -- Detectors for Position and Energy Measurement -- The Electronics of the Readout Function -- The Integration of Detectors and Their Electronics -- Detectors with Intrinsic Amplification -- Detector Technology -- Device Stability and Radiation Hardness -- Device Simulation.
Keywords: Materials science; Particle acceleration; Electrical engineering; Optical materials; Electronic materials; Materials Science; Optical and Electronic Materials; Particle Acceleration and Detection, Beam Physics; Electrical Engineering; Electronic books